PENERAPAN MODEL CONTEXTUAL TEACHING LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V MI AL-MUHAJIRIN KECAMATAN TANAH PUTIH KAB. ROKAN HILIR - Murni Wijayanti; Mahmud Alpusari; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study is a Class Action Research (CAR) conducted aims to improve learning outcomes fifth grade science students MI Al-Muhajirin by applying the models Contextual Teaching Learning (CTL). Formulation of the problem: Is the application of models Contextual Teaching Learning (CTL) can improve learning outcomes fifth grade science students MI Al-Muhajirin Menggala Sakti Kecamatan Tanah Putih Rokan Hilir. This study was conducted on 20 April 2016 until May 11, 2016 with 2 cycles. The subjects were students of class V MI Al-Muhajirin consisting 24 which is used as a data source. Data collection instrument in this thesis is the teacher and student activity sheets and learning outcomes. This thesis presents the results obtained from the study before action replay value with an average of 61.25, an increase in the first cycle with the average being 72.83. In the second cycle increased by an average of 80.17. Activities teachers in the learning process in the first cycle, the first meeting of 62.50%, and the second meeting to 75.00%. At the first meeting of the second cycle 87.50%, and the second meeting increased to 93.75%. The results of the data analysis activities of students in the first cycle of the first meeting and the second meeting of the 68.75% increase to 75.00%. In the second cycle to the first meeting of 87.50%, and the second meeting increased to 93.75%. The results of the study in class V MI Al-Muhajirin to prove that the application of learning models Contextual Teaching Learning (CTL) can improve learning outcomes fifth grade science students MI Al-Muhajirin Menggala Sakti. Keywords: models Contextual Teaching Learning (CTL), IPA Learning Outcomes